ANALISIS MINAT BELAJAR SISWA KELAS V SEKOLAH DASAR PADA MATERI SATUAN PANJANG DALAM PEMBELAJARAN MENGGUNAKAN MEDIA SCRATCH - Annisa Putri Pratiwi; Martin Bernard (IKIP Siliwangi, 2021)
This research is qualitative descriptive research that aims to see how the interest in learning elementary school students on unit length material using scratch media. The subjects of the study were 14 grade V elementary school students in West Bandung in the 2020-2021 school year. The instruments used are the assessment of the scale of students' learning interests, test tests and interviews. Then the test results and questionnaires are processed using Microsoft excel. From the results of the data that has been processed obtained the results of the study interest scale questionnaire students have a percentage of 76.26%. The results of the study from test 1 and test 2 experienced an average value change of 21.6. And based on the results of questionnaire data, test tests and interviews in students, the results of this study showed that the interest in learning grade V elementary students in long unit materials using scratch media falls into a strong category.